2022
DOI: 10.1021/acsomega.1c06878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Temperature on the Microstructure of Metakaolin-Based Geopolymer

Abstract: Currently, geopolymer is being considered as a future oil-well cement. For wellbore applications, geopolymers are initially tested at specific temperature conditions. However, an oil-wellbore may experience a sudden increase in temperature which may adversely affect geopolymer systems designed for low to moderate temperature conditions. In this work, the effect of elevated temperatures on the microstructure of the geopolymer was simulated. Metakaolin-based geopolymer systems cured at 163 °F for 48 h were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…After heating plain KGP without additives to 900 °C a series of crystalline peaks appeared in an XRD analysis [31]. Microcracks formed during geopolymer matrix dehydration/densification were filled by molten glassy phase as indicated by little-to-no open porosity in the heated samples as expected [31,50]. Figure 4 shows how the glass phase filled much larger cracks after heat treatment.…”
Section: Effect Of Initial Heat Treatmentmentioning
confidence: 74%
“…After heating plain KGP without additives to 900 °C a series of crystalline peaks appeared in an XRD analysis [31]. Microcracks formed during geopolymer matrix dehydration/densification were filled by molten glassy phase as indicated by little-to-no open porosity in the heated samples as expected [31,50]. Figure 4 shows how the glass phase filled much larger cracks after heat treatment.…”
Section: Effect Of Initial Heat Treatmentmentioning
confidence: 74%
“…Many researchers have used aluminum-silicon-rich solid waste to make geopolymer, which is a new type of green gelling material. Its main raw material can be aluminosilicate minerals occurring in nature, or it can be made from solid industrial waste with a high aluminum-silicon content [2][3][4]. Studies have shown that blast furnace slag [5], zeolite [6], metakaolin [7], fly ash [8], red mud [9], and other synthetic geopolymers have many advantages, such as high strength, low toxicity substance leaching rates, good durability, etc.…”
Section: Introductionmentioning
confidence: 99%